PERAN KONTEN BEHIND THE SCENE DI INSTAGRAM SEBAGAI MEDIA PROMOSI FILM “13 BOM DI JAKARTA” - GUSTI MUHAMMAD NAUFAL (ADISAM PUBLISHER, 2025)
The advancement of digital technology has significantly transformed promotional strategies within the film industry, particularly through the utilization of social media platforms. This study aims to examine the role of Behind the Scene content shared on Instagram as part of the promotional strategy for the Indonesian action film “13 Bom di Jakarta”, produced by Visinema Pictures. A qualitative approach is employed, using Robert N. Entman’s framing analysis model to understand how such content shapes audience perception. The findings reveal that Behind the Scene content not only transparently presents the filmmaking process but also fosters emotional engagement between the audience and the film. This type of content is perceived to enhance viewers' interest and enthusiasm through authentic and visually engaging narratives. Furthermore, Instagram proves to be an effective platform due to its ability to reach a broad audience quickly and interactively. This study asserts that in the digital era, Behind the Scene content plays a strategic role in strengthening a film’s public image and nurturing a closer relationship between creators and viewers